A Protestant theology of passion : Korean Minjung theology revisited - Küster, Volker, 1962- (Studies in Systematic Theology, 2010)
Minjung Theology is introduced here through theological biographical sketches of its main representatives. They formulated a protestant liberation theology under the South Korean military dictatorship of the 1970s and 80s. Their strong emphasis on the suffering (han) of the people (minjung) led them to the formulation of a genuine theology of the cross in Asia. Volker Küster explores the reception of Minjung Theology and raises the question what happened to it during the democratization process and the rise of globalization in the 1990s. Interpretations of art works by Minjung artists provide deep insights into these transformation processes. Prologue and epilogue abstract from the Korean case and offer a concise theory of contextual theology in an intercultural framework.